Urbanization Trends in the 21st Century - a Driver for Negative Climate, Noise and Air Quality Impacts on Urban Population - Savić, Stevan; Bjelić, Miloš; Šumarac Pavlović, Dragana; Milošević, Dragan; Dunjić, Jelena; Lazić, Lazar; Žarković, Mileta; Miljković, Tatjana (Geographica Pannonica, 2022)
"This SHORT COMMUNICATION has no abstract"